Mechanisms of cell uptake, inflammatory potential and protein corona effects with gold nanoparticles. (December 2016) - Li, Yang; Monteiro-Riviere, Nancy A
Aim: To assess inflammation, cellular uptake and endocytic mechanisms of gold nanoparticles (AuNP) in human epidermal keratinocytes with and without a protein corona.Materials & methods: Human epidermal keratinocytes were exposed to 40 and 80 nm AuNP with lipoic acid, polyethylene glycol (PEG) and branched polyethyleneimine (BPEI) coatings with and without a protein corona up to 48 h. Inhibitors were selected to characterize endocytosis.Results & conclusion: BPEI-AuNP showed the greatest uptake, while PEG-AuNP had the least. Protein coronas decreased uptake and affected their mechanism. AuNP uptake was energy-dependent, except for 40 nm lipoic-AuNP. Most AuNP were internalized by clathrin and lipid raft-mediated endocytosis, except for 40 nm PEG was by raft/noncaveolae mediated endocytosis. Coronas inhibited caveolae-mediated-endocytosis with lipoic acid and BPEI-AuNP and altered 40 nm PEG-AuNP from raft/noncaveolae to clathrin. Inflammatory responses decreased with a plasma corona. Results suggest protein coronas significantly affect cellular uptake and inflammatory responses of AuNP.